Peculiarities of socio-economic portrait of the subjects of youth entrepreneurship in the national economy - Khussainova, Zh.S.; Zhartay, Zh.M.; Adilova , Zh.G. (BUKETOV BUSINESS REVIEW, 2019)
In the article the socio-economic portrait of the subject of youth entrepreneurship in Kazakhstan was considered. Youth entrepreneurship is defined as a tool to ensure the growth of employment, the involvement of young people in to economic activity, their socialization and self-realization. The development of this direction allows to use the creative potential of the younger generation in the interests of innovative development of the country. The authors present the results of sociological analysis conducted in the framework of the topic among young entrepreneurs and students of the Republic of Kazakhstan. The subjects determining the position and opportunities of young people in the field of entrepreneurship are analyzed. Based on the data of sociological studies, it is concluded that there are formed social stereotypes in the public consciousness that prevent and impede the entry of young people into the business environment and reduce their readiness to organize independent business activities. The socio-economic qualities of the subject of youth entrepreneurship, such as leadership qualities, creativity, organizational skills, purposefulness, communication skills that contribute to the development of the system of state support and support of young people who want to organize their business were revealed. The conclusion that only the implementation of common efforts of the state, business, civil society (NGO) institutions will contribute to the development of youth entrepreneurship is substantiated.